Health-related quality of life of patients with rheumatoid arthritis on tocilizumab, adalimumab, and etanercept in Saudi Arabia: a single-center cross-sectional study - Alotaibi, Amjad M.; Albahdal, Areej S.; Abanmy, Norah; Alwhaibi, Monira; Asiri, Yousif; AlRuthia, Yazed (Frontiers in Pharmacology, 2023)
The aim of this study was to assess the quality of life (QOL) of patients with rheumatoid arthritis (RA) on tocilizumab versus other commonly used monoclonal antibodies (mAbs) (e.g., adalimumab and etanercept).This was an interview-based cross-sectional study. Adult RA patients (≥18 years) with a disease duration of at least one year were included in the study. The Arabic version of EUROQOL (EQ-5D-5L) was used to assess the QOL of RA patients on mAbs. Multiple linear regression was conducted to examine the impact of tocilizumab versus other mAbs on the visual analog scale (VAS) score controlling for age, disease duration, treatment duration, gender, number of comorbidities, and the use of steroids.The number of patients who met the inclusion criteria and consented to be interviewed was 105 patients (tocilizumab (n=37), adalimumab (n=31), and etanercept (n=37)). No significant differences in the scores of the five EQ-5D-5L domains across different mAbs. Although the VAS score of patients on tocilizumab was numerically higher compared to their counterparts on adalimumab or etanercept (69.19 vs. 62.79) this was not statistically significant controlling for age, gender, disease and treatment durations, number of comorbidities, and the utilization of steroids (β=4.26, 95% CI: [-8.84-17.36], p=0.52).The use of tocilizumab did not seem to result in better QOL among RA patients.Future studies with larger sample sizes and more robust designs should be conducted to confirm or refute these findings.